Eco-efficiency in early design decisions: A multimethodology approach. (10th February 2021) - Belucio, Matheus; Rodrigues, Carla; Antunes, Carlos Henggeler; Freire, Fausto; Dias, Luís C.
Abstract: Eco-efficiency is a key concept encompassing economic and environmental aspects to promote a more efficient use of resources and lower emissions. An eco-efficiency perspective in the design of products and services is thus essential in the pursuit of sustainability. This article proposes a novel decision-support methodological approach to assess the environmental impacts and costs in early design stages, aimed at providing informed recommendations to designers, manufacturers and decision-makers. This multimethodology approach integrates a streamlined life-cycle environmental and cost assessment with a data envelopment analysis (DEA) model that derives eco-efficiency ratios and compares alternative designs, without the need to subjectively weigh the different environmental and cost life-cycle metrics. A linear regression model is then used to indicate the most influential decision variables. This approach was applied to a retrofit process of a historic residential building located in Southern Europe. The metrics used to assess the design parameters are: climate change, acidification, eutrophication, non-renewable primary energy, and net present value. A sensitivity analysis on the decarbonization of the electricity mix was also performed. The multimethodology offers valuable guidance to allow decision-makers to progressively specify the decision variables in an iterative way, using robust methods allowing for the statistical validation of results. The case study revealed robust empirical results for building retrofits in Southern European climates, indicating that the variables that most impact eco-efficiency (in both short and long-term) are roof insulation thickness and material followed by exterior wall insulation material. After three variables specification, the average eco-efficiency always increased, with higher gains obtained for the scenarios with the current electricity mix (22–25% increase) and more modest gains obtained for the electricity decarbonization scenarios (8–15% increase). Highlights: A multimethodology decision support tool combining LCA, DEA and linear regression. - Multimethodology offers more information in early design for sustainable decisions. - Identify most influential variables on eco-efficiency of buildings retrofits. - Specifying three variables increased average ecoefficiency by more than 20%.